P02.16 Evaluating the therapeutic potential of anti-CD19 chimeric antigen receptor T-cells in a murine model of human primary CNS lymphoma using long-term in vivo imaging. (19th September 2018) - Mulazzani, M; Fräßle, S; Langer, S; von Mücke-Heim, I; Buchholz, V; Straube, A; Busch, D; von Baumgarten, L
Abstract: Background: Multi-agent chemotherapy has led to an improved survival in patients suffering from primary CNS lymphoma (PCNSL). Still, long-term disease remission is rare and therapy associated side effects are common. In recent years, a growing body of evidence has demonstrated the therapeutic potential of chimeric antigen receptor (CAR) T-cells in systemic B-cell malignancies. Studies on CAR T-cells targeting human CD19 ( CD19 CAR T-cells), a pan B-cell antigen also expressed by PCNSL cells, have produced promising clinical results. However, little is known about the interaction of CD19 CAR T-cells and PCNSL cells in vivo . The aim of this study was to evaluate the proliferation, tumour infiltration and long-term persistence of CD19 CAR T-cells as well as the therapeutic effect on PCNSL growth. Material and Methods: We established a novel PCNSL model in T-cell deficient nude mice. After microsurgical implantation of a cranial window, red fluorescent, human B-cell lymphoma cells were injected stereotactically into the animal's cortex. Once a tumour had grown to a diameter of 500 µm, the mice were allocated either to the treatment or to the control group. In the treatment group, green fluorescent CD19 CAR T-cells were injected in close proximity to the PCNSL into the cortex. Animals of the control group were injected with mock CAR T-cells, which lacked the extracellular domain of the CAR. To visualise the interactions of CAR T-cells with lymphoma cells, multiple two photon microscopy sessions were conducted over several weeks. Results: The in vivo interaction of CD19 CAR T-cells and tumour cells led to proliferation of CD19 CAR T-cells in the treatment group. Within a few days after injection, CD19 CAR T-cells resided adjacent to the tumour and infiltrated tumorous tissue in large quantities. In the treatment group, significant tumour growth inhibition and disease regression was observed. In contrast, mock CAR T-cells barely proliferated and only marginally infiltrated the tumour or eliminated tumour cells. Long-term persistence of CD19 CAR T-cells was detected in the brain, lymph nodes and blood, even after tumour regression. Conclusion: Our study illustrates the in vivo characteristics of CD19 CAR T-cells, their anti-tumorous effect and long-term persistence. These results emphasize the therapeutic potential of CD19 CAR T-cells in PCNSL. Based on these results, clinical studies to assess the efficacy and safety of CD19 CAR T-cells in humans suffering from PCNSL are highly warranted.